Elaboração de um modelo de localização de cargas unitizadas agroindustriais em pátios portuários: aplicação ao caso do terminal portuário do Pecém - Souza, Fabio Abreu Freitas de (2002)
The Ports constitute instruments to the support of the economy of many regions where they are located; they are extremely important areas of the export commerce and contribute significantly to the development of the national economy. Fundamental on the logistical part of transportation, the harbors aggregate the values of the goods produced in its regions and fulfill a strategic part on their own commerce since they catalyze economical flows from imports and exports. The necessity of development of the exterior commerce and contribute to the economical growth requests a major responsibility to the Ports of all countries, and mainly to those who are located in developing countries since they need a high level of efficiency and technology to function. Trying to put this idea into actions, this research shows a mathematically consistent, practical and easy application to optimize the location of cargos at the Port patios, emphasizing the reefer container that transport agribusiness cargos, minimizing the time consumed to dislocate these inside the Port area. This emphasis to the reefer containers is due the necessity verified with bibliographical research and visits at some ports to minimize the losses suffered for one of the principal Brazilian export sectors, the agribusiness. The optimal location model was applied to the Pecém Port Terminal to optimize his physical arrange.